The Study of Prevalence and Factors Related to Smoking of Thai Families during the COVID-19 Pandemic - Araya Haupala (2022)
Background: COVID-19 is a viral respiratory infection causing severe acute respiratory syndrome. Smoking is a major cause of non-communicable diseases and causing death of Thai people in the past 10 years. COVID-19 patients with a history of smoking could experience severe symptoms. Objective: To study the prevalence and related factors of smoking in Thai families during the COVID-19 pandemic. Materials and Methods: The present study was a survey to explore the prevalence and factors of smoking in Thai families. Results: During the COVID-19 pandemic, 41.5% of Thai family had a family member that smoked. The factors affecting smoking in the family were the extended family, which was statistically significantly more than in the single family at 1.53 times (adjusted OR 1.53, 95% CI 1.21 to 1.94). Monthly family income, insufficient income, or no income affected smoking in the family statistically significantly more than expenditures at 2.41 times (adjusted OR 2.41, 95% CI 1.38 to 4.22). Monthly family income that changed to insufficient income for some months affected smoking in the family statistically significantly more than expenditures at 2.29 times (adjusted OR 2.29, 95% CI 1.31 to 3.98). Monthly moderate family income with just enough each month affected smoking in the family statistically significantly 2.02 times higher than in families with higher income (adjusted OR 2.02, 95% CI 1.15 to 3.55). At least one type of the domestic violence such as mental, physical, or sexual violence in the family affected smoking in the family during the COVID-19 pandemic more than in the non-violent families 1.31 times (adjusted OR 1.31, 95% CI 1.04 to 1.65). Conclusion: The present study showed the prevalence of smoking in Thai families during the COVID-19 pandemic has relationship with family characteristics, domestic violence, and monthly income.